Ambiguity of the Offense Regarding Obstruction of Justice in Corruption Cases in Indonesia - Antoni Antoni; Megawati Barthos (Syntax Idea)
Obstruction of justice, or acts that impede the legal process, is a serious threat to law enforcement, particularly in corruption cases. In Indonesia, this act is regulated under Article 21 of Law No. 31 of 1999 concerning the Eradication of Corruption Crimes, amended by Law No. 20 of 2001. This study aims to analyze the ambiguity of the offense of Obstruction of Justice and examine efforts to address the ambiguity of the offense in corruption crimes. Through a juridical-normative method, this article investigates the unclear legal regulation of obstruction of justice in corruption offenses, as well as efforts to create legal certainty regarding Obstruction of Justice.